Spatial Structure of Morphological and Neutral Genetic Variation in Brook Trout. Issue 3 (14th April 2015) - Kazyak, David C.; Hilderbrand, Robert H.; Keller, Stephen R.; Colaw, Mark C.; Holloway, Amanda E.; Morgan, Raymond P.; King, Tim L.
Abstract: Brook Trout Salvelinus fontinalis exhibit exceptional levels of life history variation, remarkable genetic variability, and fine‐scale population structure. In many cases, neighboring populations may be highly differentiated from one another to an extent that is comparable with species‐level distinctions in other taxa. Although genetic samples have been collected from hundreds of populations and tens of thousands of individuals, little is known about whether differentiation at neutral markers reflects phenotypic differences among Brook Trout populations. We compared differentiation in morphology and neutral molecular markers among populations from four geographically proximate locations (all within 24 km) to examine how genetic diversity covaries with morphology. We found significant differences among and/or within streams for all three morphological axes examined and identified the source stream of many individuals based on morphology (52.3% classification efficiency). Although molecular and morphological differentiation among streams ranged considerably (mean pairwise F ST : 0.023–0.264; pairwise P ST : 0.000–0.339), the two measures were not significantly correlated. While in some cases morphological characters appear to have diverged to a greater extent than expected by neutral genetic drift, many traits were conserved to a greater extent than were neutral genetic markers. Thus, while Brook Trout exhibit fine‐scale spatial patterns in both morphology and neutral genetic diversity, these types of biological variabilities are being structured by different ecological and evolutionary processes. The relative influences of genetic drift versus selection and phenotypic plasticity in shaping morphology appear to vary among populations occupying nearby streams.